Strategies for Developing the Professionalism of Elementary School Teachers Through Human Resource Management at SDN 158 Palembang - Rika Apriana; AdeAkhmad Saputra (GENIUS: Journal of Elementary Pedagogy and Innovation Studies, 2026)
This study examines the implementation of human resource (HR) management strategies in enhancing teacher professionalism at SD Negeri 158 Palembang through George R. Terry’s POAC management functions: planning, organizing, actuating, and controlling. A qualitative descriptive approach was employed, with data collected through observations, interviews, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that POAC-based HR management was implemented through systematic workforce planning, competency-based task allocation, continuous professional development, academic supervision, principal support and motivation, and regular monitoring and evaluation of teacher performance. These strategies positively influenced teacher discipline, responsibility, collaboration, creativity, and professionalism in classroom practices. The study also demonstrates the relevance of POAC in strengthening HR management at the elementary school level. Despite these achievements, challenges remain, including limited facilities, unequal technological competencies, and restricted access to professional training. Overall, sustainable and structured HR management significantly contributes to improving teacher professionalism and educational quality.